Analisis Akuntabilitas Dan Transparansi Laporan Keuangan Berdasarkan SAK EP Di Koperasi Karyawan RS Toeloengredjo - Nandasari, Silvania Dian (JCA (Jurnal Cendekia Akuntansi), 2026)
The Financial Accounting Standards for Private Entities (SAK EP), effective January 1, 2025, mandate that business entities, including cooperatives, deliver comprehensive financial reports that accurately reflect economic realities. A qualitative study focused on the HVA Toeloengredjo Hospital Employees' Cooperative evaluates the enforcement of accountability and transparency in financial reporting under these new standards. The findings indicate a commendable level of accountability, demonstrated through adherence to Articles of Association (AD/ART) targets, effective internal controls, and thorough financial disclosures to stakeholders. While accounting policies, such as the Cost Model for fixed assets and FIFO inventory methods, have been established, financial reporting remains predominantly manual and does not fully comply with SAK EP. Key inconsistencies include the omission of the Cost of Goods Sold account in income statements, violating the Matching Principle, and the lack of an allowance for doubtful accounts. Challenges hindering alignment with SAK EP include insufficient technological infrastructure, limited knowledge of updated standards, and lack of human resource preparedness. To address these issues, enhanced training for staff and investment in accounting information systems are essential to improve compliance with Good Corporate Governance (GCG) principles. This research aims to motivate cooperatives to better the quality and adherence of their financial reporting in accordance with SAK EP. Keywords: Accountability, Transparency, Financial Reporting, Private Entity Financial Accounting Standards, Cooperatives